2010
DOI: 10.1107/s0021889810038264
|View full text |Cite
|
Sign up to set email alerts
|

Field-induced phase transition in Bi1/2Na1/2TiO3-based lead-free piezoelectric ceramics

Abstract: The origin of the electric field-induced strain in the polycrystalline ceramic 0.92Bi 1/2 Na 1/2 TiO 3 -0.06BaTiO 3 -0.02K 1/2 Na 1/2 NbO 3 was investigated using in situ high-resolution X-ray and neutron diffraction techniques. The initially existing tetragonal phase with pseudocubic lattice undergoes a reversible phase transition to a significantly distorted rhombohedral phase under electric field, accompanied by a change in the oxygen octahedral tilting from a 0 a 0 c + to a À a À a À and in the tilting ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
120
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 182 publications
(135 citation statements)
references
References 41 publications
14
120
1
Order By: Relevance
“…The origin of the large electromechanical response of incipient piezoelectrics is generally attributed to an electric field induced phase transition. [140][141][142][143][144][145][146][147] Figure 2.14 at point displays an ergodic relaxor state, as previously discussed. For BNT-based lead-free incipient piezoelectrics, it was demonstrated that the electric field induced phase transition coincides with the inflection point of the strain output 148 and the transformation is followed by switching of the newly created domains.…”
Section: Lead-free Relaxor Ferroelectricsmentioning
confidence: 61%
See 4 more Smart Citations
“…The origin of the large electromechanical response of incipient piezoelectrics is generally attributed to an electric field induced phase transition. [140][141][142][143][144][145][146][147] Figure 2.14 at point displays an ergodic relaxor state, as previously discussed. For BNT-based lead-free incipient piezoelectrics, it was demonstrated that the electric field induced phase transition coincides with the inflection point of the strain output 148 and the transformation is followed by switching of the newly created domains.…”
Section: Lead-free Relaxor Ferroelectricsmentioning
confidence: 61%
“…In contrast, other BNT-based materials feature passive phase transformations as a consequence of compressive stresses. 141,142 Since stresses seem to play a secondary role, the non-zero intensity of the ½(311) pc SSR indicates that the electric field is a conjugate thermodynamic variable of the octahedral tilt angle ∅. This entails that the correlation length of ( − − − ) tilting increases considerably upon application of electric field.…”
Section: Mesoscopic Treatmentmentioning
confidence: 99%
See 3 more Smart Citations